A 3-channel CCD photometer at the Xinglong Observatory - Mao, Yong-Na; Lu, Xiao-Meng; Wang, Jian-Feng; Jiang, Xiao-Jun (Research in astronomy and astrophysics, 2013)
We describe the design and construction of a new rapid 3-channel CCD photometer, dedicated to simultaneous multicolor photometric observations of rapidly variable objects. This photometer is equipped on the 1-meter telescope at the Xinglong Observatory. It allows simultaneous imaging within fields of view of 18.81′×18.8′, 18.2′×17.6′ and 9.2′×9.2′ in the Sloan Digital Sky Survey＇s g′, r′ and i′ bands, respectively. The results of its calibration and performance are reported.